Wave system fitting: A new method for force measurements in shock tunnels with long test duration. (October 2015) - Luo, Changtong; Wang, Yunpeng; Wang, Chun; Jiang, Zonglin
Abstract: Force measurements in shock tunnels are difficult due to the existence of vibrations excited by a sudden aerodynamic loading. Accelerometer inertia compensation could reduce its negative effect to some extent, but has inherent problems. A new signal decomposition method, wave system fitting (WSF), is proposed to remove vibration waves of low frequency. The WSF is accelerometer-free. It decomposes the balance signal and can separate vibration waves without the influence on the DC component, and it does work no matter the cycle of the sample signal is complete or not. As a standard signal post-processing tool in JF-12, the application results show that it works reliably with high accuracy, and it can also explain puzzling signals encountered in JF-12. WSF method is especially useful and irreplaceable whenever only a few cycles of a periodic signal could be obtained, as is usual for shock tunnels. Abstract : Highlights: This study proposes a new method for force measurements in shock tunnels with long test duration. It can separate and remove vibration waves of low frequency from the balance signal to improve the measurement accuracy. It can also explain puzzling signals encountered in shock tunnel JF-12. It is an accelerometer-free method, and it does work no matter the cycle of the sample signal is complete or not. It is especially useful whenever only a few cycles of periodic signal could be obtained, as is usual for shock tunnels.